The Border and the Sign - Safaryan, Anush (History and Culture, 2025)
The act of demarcating a border is not merely a geographical, military, political, or economic phenomenon; it is also a cultural one. It functions not only as a defense mechanism but also as a unique communication system, incorporating the placement of certain structures and signs along the border. The article goes on to explore the function of these signs, their location, and the reasons for their specific use. The article then attempts to classify these signs, present their architectural and iconographic features, and highlight their ritualistic functions at the border. The article also examines the organisational, ideological, and cultural potential of these signs for border communities and settlements. The multifaceted nature of border signs is also discussed, insofar as they are not merely perceived as territorial delimiters, but also studied for their role as unique symbols of nationalism, identity, and communication. A semiotic analysis of border markings is undertaken, exploring the symbolic meanings behind various signs and how they shape the cultural and political discourse of the border. The research focuses primarily on the Armenian-Azerbaijani border, drawing parallels with examples from the Tavush, Gegharkunik, and Syunik regions. The study places particular emphasis on the examination of religiously significant border markers or indicators, such as khachkars and cross-based structures, as these types of signs frequently become primary targets during periods of conflict.